PENGARUH TEKNOLOGI PEMBERI PAKAN IKAN OTOMATIS TERHADAP KUALITAS HASIL BUDIDAYA IKAN NILA: PENGARUH TEKNOLOGI PEMBERI PAKAN IKAN OTOMATIS TERHADAP KUALITAS HASIL BUDIDAYA IKAN NILA - Ali Rizal Chaidir; Dedy Wahyu Herdiyanto; Andrita Ceriana Eska; Guido Dias Kalandro (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2025)
Fish culture has an important role in achieving food security in Indonesia. Tilapia is one of the fish that can be obtained through aquaculture activities. Several factors influence the growth of tilapia, such as water quality, feeding process, and quality of the feed provided. Too little feed can cause tilapia to experience slow growth, while too much feed can cause poor water quality because food is not eaten or eaten too late. The objective of this study is to analyze the use of an automatic feeder compared to conventional methods. The results can be a viable option for specific fish culture practices to achieve optimal yields. The results of the application of technology show that the feed conversion ratio reached 97.6%, the survival rate reached 94.4%, and the specific growth rate reached 3.58%. This is better compared to several other treatments in fish culture, so it can result in faster harvest results with efficient use of feed and maximum harvest quantity.